含间隙弧面凸轮分度机构的ADAMS动力学仿真 - 于春玲 (Jixie chuandong)
Profile surface data of cam is generated by Visual C++,the entity model is built in Pro/E and transformed into a virtual prototype in Adams through interface Mechanism/Pro,at last,the motion simulation is carried out.It is proved that clearance existing in globoidal cam brings impact and vibration,and angular acceleration of the indexing plate is not continuous,and the effect of the moment of inertia of the load is increased with higher cam speed.